THE EFFECT OF SCAFFOLDING STRATEGY WITH WORKSHEET ON STUDENT SCIENCE PROSCESS SKILLS: EFEK STRATEGI SCAFFOLDING DENGAN LEMBAR KERJA TERHADAP KETERAMPILAN PROSES SAINS SISWA - Annisa Kamila Insani; I Made Astra; Mutia Delina (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
The scaffolding strategy is a strategy that makes students more active in learning by providing step-by-step assistance from teachers and peer tutors so that it can influence student’s science process skills. The scaffolding strategy also makes learning in class more active because students are more confident in voicing their opinions. Implementation of the scaffolding strategy by providing assistance at the student learning stage, so that students can influence students' science process skills.The method that will be used in researching student workseet assisted scaffolding is a quasi-experimental method with a non-equivalent control group pretest-posttest design, which divides the research sample into an experimental group and a control group. The data in this study was obtained based on the results before the test, results after the test, observation sheets on learning implementation, and documentation.